A novel mid-infrared thermal emitter with ultra-narrow bandwidth and large spectral tunability based on the bound state in the continuum. (11th October 2021) - Sun, Kaili; Cai, Yangjian; Han, Zhanghua
Abstract: The development of efficient, compact and low-cost mid-infrared (MIR) sources with easy manufacturing is vital in a variety of applications including gas sensing, thermal photovoltaic power generation, infrared imaging, among others. In this work, we demonstrate that a novel type of MIR thermal emitters with ultra-narrow bandwidth and broad spectral tunability can be realized based on a new operation principle employing the concept of bound state in the continuum (BIC). Using an elaborately designed structure composed of two interdigitated gratings with the same pitch and different stripe width on a slab supported by a conducting substrate, the quasi-BIC mode with both ultra-high Q-factor (>10 4 ) and large absorbance/emittance can be achieved, resulting from the destructive interference between the couplings of two guided-mode resonances back to free space. At the operation wavelength of 7.7851 μ m, even when the metal dissipation is considered, a near-unity emission at resonance with the full-width at half-maximum less than 0.3 nm is numerically presented, which is three orders of magnitude narrower than conventional metallic metamaterial based thermal emitters. By applying a geometrical scaling of the structure, the operation wavelength can be flexibly extended to other wavelengths of the MIR region. The presented novel thermal emitter with economic advantages and high performances of both ultra-narrow bandwidth and broad wavelength-tunability, will make great impact in practical applications.